Robust H∞ switched control for uncertain linear systems via chattering free static output feedback∗ - Faria, Flavio A. [UNESP]; Elias, Leandro J.; Cardim, Rodrigo [UNESP]; Oncoy, Dante J. S. [UNESP]; Oliveira, Vilma A. (Institute of Electrical and Electronics Engineers (IEEE), 2024)
This work proposes a switched control strategy to attenuate the effect of L2 type disturbances on the output performance of uncertain linear systems. The switched controller improves the control performance and reduces the conservatism of existing solutions. Stabilization conditions are given in terms of LMIs which are designed such that the proposed solution guarantees an H∞ cost and be free of chattering. The efficiency of the stabilizing conditions are evaluated by numerical examples.